«DRAMATIZATION» OF V/ STEFANYK’S NOVELLAS IN THE FOCUS OF NARRATOLOGICAL METHODOLOGY - Kazanova, O. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The research elucidates the peculiarities of functioning of narrative forms of Vasyl Stefanyk’s novellas that affected dramatization of his prose and modification of genre forms of the writer’s creations. It is argued that with the employment of methods of dramaturgical poetics (dramatization of actions, dialogue and monologue speech, etc.) the author of novellas psychologized his creations, gave the prosaic narrations tension bordering on the genuine folk-philosophical tragedy.